Influence of the nature of the metal ion on the rate of reduction of coordinated azomethine group - (:unkn) unknown (MAIK NAUKA/INTERPERIODICA/SPRINGER, 2007)
The kinetics of reduction of the azomethine bond in various Schiff bases and their transition metal complexes with sodium borohydride in dimethylformamide and ethanol solutions was studied. The reduction rate depends on both the structure of the starting Schiff bases and the nature of the metal ion. In transition metal N-phenylsalicylaldiminates, the rate of reduction of the azomethine group increases in the order Zn(II) < Ni(II) < Cu(II) < Co(II) < VO(II) < Mn(II). Similar trend is observed in other series of metal complexes with Schiff bases. The revealed trends are opposite to the Irving-Williams series of stability of complexes. This fact suggests that the major factor affecting the rate of reduction of the coordinated azomethine bond is the strength of its bonding with the metal ion. Depending on particular metal ion, the complexation can either decelerate or accelerate the reduction.
Keywords: ENANTIOSELECTIVE BOROHYDRIDE REDUCTION; COBALT(II) COMPLEX CATALYSTS; KETONES; DERIVATIVES; IMINES